(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
In the article the views of domestic scholars-agrarians on the role of agricultural sector of the country in ensuring sustainable development of the national economy and the expediency of Ukraineʼs accession to the World Trade Organization are investigated. Proved, that Ukraine, with its fertile soils, can provide their own food market and export them. The analysis of the efficiency the functioning of the agricultural sector of Ukraine before and after its accession to the World Trade Organization is carried out. Revealed, that the Ukrainian agricultural complex after Ukraineʼs accession to the WTO, even in the financial crisis, has provided the increasing agricultural production, what demonstrated its resilience to external financial and economic shocks. Measures to expand of state support for domestic agrarians, that include a increased financial subsidies, protection of domestic agricultural market from unfair competition from other countries and the assistance to export of domestic agricultural products to international markets are offered